The role of tenofovir alafenamide in future HIV management. (May 2016) - Antela, A; Aguiar, C; Compston, J; Hendry, BM; Boffito, M; Mallon, P; Pourcher‐Martinez, V; Di Perri, G
Abstract : HIV infection has become a chronic condition rather than an acute life‐threatening disease in developed countries, thanks to consistent innovation and evolution of effective interventions. This has altered HIV management and created new challenges. People living with HIV (PLWHIV) are living longer and so encounter comorbidities linked not only with their disease, but also with ageing, lifestyle and chronic exposure to antiretroviral therapy (ART). Although longevity, viral suppression and the prevention of viral transmission remain key goals, more needs to be achieved to encompass the vision of attaining an optimum level of overall health. Treatment choices and management practices should ensure patients' long‐term health with minimal comorbidity. Treatments that balance optimal efficacy with the potential for improved long‐term safety are needed for all patients. In this review, we consider the evolution and development of tenofovir alafenamide (TAF), a novel prodrug of tenofovir which offers high antiviral efficacy at doses over ten times lower than that of tenofovir disoproxil fumarate (TDF). Emerging clinical data suggest that elvitegravir, cobicistat, emtricitabine and TAF (E/C/F/TAF) as a single‐tablet regimen offers highly effective viral suppression in treatment‐naïve and treatment‐experienced patients with an improved renal and bone safety profile compared with TDF, this having been demonstrated in diverse groups including patients with existing renal impairment and adolescents. The profile of TAF identifies it as an agent with a promising role within future ART regimens that aim to deliver the vision of undetectable viral load, while requiring less monitoring and having a safety profile designed to minimize comorbid risks while supporting good long‐term health.